Polyacrylic acid particles

Polyacrylic acid-based fine particles with controlled composition and diameter, produced via living radical polymerization, address the issues of high dosage and poor transparency, achieving efficient thickening and clarity in aqueous solutions.

JP7619276B2Active Publication Date: 2025-01-22TOAGOSEI CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021556109
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-15
Filing Date
2020-11-10
Publication Date
2025-01-22
Estimated Expiration
2040-11-10

AI Technical Summary

Technical Problem

Existing polyacrylic acid-based fine particles require large amounts for effective thickening and exhibit poor transparency in aqueous solutions.

Method used

Developed polyacrylic acid-based fine particles with a specific composition and controlled particle diameter, including a high content of acrylic acid structural units and a narrow molecular weight distribution, achieved through living radical polymerization, allowing for high viscosity and transparency at low concentrations.

Benefits of technology

The solution enables high thickening properties and excellent transparency in aqueous solutions with reduced particle size and improved dispersion stability, facilitating efficient use at lower particle concentrations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619276000001
    Figure 0007619276000001
  • Figure 0007619276000002
    Figure 0007619276000002
  • Figure 0007619276000003
    Figure 0007619276000003
Patent Text Reader

Abstract

Provided are polyacrylate-based fine particles that have thickening properties enabling exhibition of high viscosity even when being added in a further less amount and that allows an aqueous solution to have excellent transparency. The polyacrylate-based fine particles contain a polyacrylate-based polymer including 10 mass% or more of a structural unit derived from acrylic acid with respect to the total mass of non-crosslinkable structural units, and have a mean particle diameter of 0.01-0.20 µm which is the average value of diameters of 400 particles in an image observed by using a field emission type scanning electron microscope.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This specification relates to polyacrylic acid based microparticles.

[0002] (Cross-reference to related applications) This application is a related application of Japanese patent application No. 2019-207466, filed on November 15, 2019, and claims priority based on this application, and incorporates all contents of this application by reference. [Background technology]

[0003] Polyacrylic acid-based microparticles are widely used as thickeners, viscosity modifiers, anti-settling agents for pigments, dispersion stabilizers for metal powders, etc. In particular, when used as an aqueous thickener, when the polymer is linear, it has a spinnability and feels sticky, but as the degree of crosslinking increases, the spinnability decreases and it feels fresh. Therefore, linear (or slightly crosslinked) polyacrylic acid-based microparticles are used in applications where spinnability is required, and crosslinked polyacrylic acid-based microparticles are often used in applications where spinnability is not required and freshness is required. Crosslinked polyacrylic acid-based microparticles also have the advantage of being able to achieve high thickening with a small amount of use.

[0004] Here, various crosslinked polyacrylic acid-based particles are known. For example, polyacrylic acid-based particles having acrylic acid, methyl methacrylate, and divinylbenzene as constituent monomer units have been reported (Patent Document 1). The average particle diameter of these polyacrylic acid-based particles is described as 0.7 μm as observed with a scanning electron microscope. Polyacrylic acid-based particles having acrylic acid and divinylbenzene as constituent monomer units have also been disclosed, and the average particle diameter thereof is described as 3.5 μm as observed with a scanning electron microscope (Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 04-279604 [Patent Document 2] JP 2006-282772 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, when these polyacrylic acid-based microparticles are used as aqueous thickeners, the amount of polyacrylic acid-based microparticles added is large relative to the target viscosity, resulting in poor thickening properties. In addition, the transparency of the aqueous solution of the polyacrylic acid-based microparticles is poor.

[0007] In view of the above circumstances, the present specification provides polyacrylic acid-based fine particles that have a thickening property that enables high viscosity to be achieved with even a smaller amount added, and that have excellent transparency in aqueous solutions. [Means for solving the problem]

[0008] The present inventors have conducted various studies on polyacrylic acid-based microparticles and found that the average particle size of the microparticles significantly contributes to the thickening effect and the transparency of an aqueous solution. Based on this finding, the present specification provides the following means.

[0009] [1] Polyacrylic acid-based microparticles, The polyacrylic acid-based microparticles contain a polyacrylic acid-based polymer containing 10% by mass or more of structural units derived from acrylic acid relative to the total mass of non-crosslinkable structural units, Polyacrylic acid-based microparticles having an average particle size of 0.01 μm or more and 0.20 μm or less, as calculated by averaging the particle sizes of 400 particles in an image observed with a field emission scanning electron microscope. [2] The polyacrylic acid microparticles according to [1], wherein the average particle size is from 0.01 μm to 0.15 μm. [3] The polyacrylic acid microparticles according to [2], wherein the average particle diameter is 0.01 μm or more and 0.10 μm or less. [4] The polyacrylic acid-based microparticles according to any one of [1] to [3], wherein the polymer contains 20 mass % or more of structural units derived from the acrylic acid. [5] The polyacrylic acid-based microparticles according to any one of [1] to [4], wherein the polymer is neutralized to a degree of neutralization of 50 mol % or more and 100 mol % or less. [6] The polyacrylic acid microparticles according to any one of [1] to [5], wherein the polymer is crosslinked with a crosslinkable monomer, and the amount of the crosslinkable monomer used is 0.03 mol % or more and 2 mol % or less based on the total amount of the non-crosslinkable monomers. [7] The polyacrylic acid-based microparticles according to any one of [1] to [6], wherein the polymer contains a polymer chain having living radical polymerization activity. [8] The polyacrylic acid microparticles according to [7], wherein the molecular weight distribution of the polymer chains is 2.0 or less. [9] The polyacrylic acid microparticles according to [7] or [8], wherein the content of the polymer chains in the polymer is from 0.3% by mass to 30% by mass.

[10] Polyacrylic acid microparticles, The polyacrylic acid-based microparticles contain a polymer containing 20% ​​by mass or more of structural units derived from acrylic acid relative to the non-crosslinked structural units thereof, The polyacrylic acid-based particles, wherein a 1.2% by mass aqueous solution of the polyacrylic acid-based particles has a viscosity of 5,000 mPa·s or more and a haze value of 50% or less.

[11] A thickener comprising the polyacrylic acid microparticles according to any one of [1] to

[10] . DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The disclosure of this specification relates to polyacrylic acid-based microparticles. The polyacrylic acid-based microparticles disclosed in this specification (hereinafter, simply referred to as polymer microparticles or the present microparticles) have excellent thickening effect and aqueous solution transparency that can exhibit high thickening properties at low concentrations. Therefore, it is easy to provide an aqueous medium with high viscosity and high transparency.

[0011] Representative and non-limiting specific examples of the present disclosure will be described in detail below. This detailed description is intended simply to provide those skilled in the art with details for implementing the preferred examples of the present disclosure, and is not intended to limit the scope of the present disclosure. In addition, the additional features and inventions disclosed below can be used separately or together with other features and inventions to provide further improved "polyacrylic acid-based microparticles".

[0012] In addition, the combinations of features and steps disclosed in the following detailed description are not essential to the implementation of the present disclosure in the broadest sense, but are described only to specifically illustrate representative embodiments of the present disclosure. Furthermore, the various features of the representative embodiments described above and below, and the various features of those described in the independent and dependent claims, do not have to be combined in the specific examples described herein or in the order listed to provide additional and useful embodiments of the present disclosure.

[0013] All features described in the specification and / or claims are intended to be disclosed individually and independently of one another as limitations to the original disclosure and claimed particulars, apart from any configuration of features described in the examples and / or claims. Furthermore, all numerical ranges and group or aggregate descriptions are intended to disclose their intermediate configurations as limitations to the original disclosure and claimed particulars.

[0014] Various embodiments disclosed in this specification will be described in detail below. In this specification, "(meth)acrylic" means acrylic and / or methacrylic, "(meth)acrylate" means acrylate and / or methacrylate, and "(meth)acryloyl group" means acryloyl group and / or methacryloyl group.

[0015] The composition of the polyacrylic acid polymer constituting the polyacrylic acid microparticles (hereinafter also simply referred to as the present microparticles) and the average particle size of the present microparticles will be described below, and then the method for producing the present microparticles will be described.

[0016] (Polyacrylic acid particles) The microparticles of the present invention contain a polyacrylic acid polymer (hereinafter also referred to as the present polymer). Typically, the microparticles are composed of the present polymer. The present polymer may be composed only of a non-crosslinkable structural unit derived from a non-crosslinkable monomer, or may be composed of a non-crosslinkable structural unit and a crosslinkable structural unit derived from a crosslinkable monomer.

[0017] (Structural unit derived from acrylic acid) The polymer comprises at least a structural unit derived from acrylic acid, which is classified as a non-crosslinkable monomer and constitutes a non-crosslinkable structural unit.

[0018] The carboxyl group of the structural unit derived from acrylic acid may be in the form of a salt. Here, the salt is an alkali metal salt, an alkaline earth metal salt, an ammonium salt, or an organic amine salt. Specifically, alkali metal salts such as sodium salt, lithium salt, potassium salt, rubidium salt, and cesium salt; alkaline earth metal salts such as magnesium salt, calcium salt, strontium salt, and barium salt; organic amine salts include alkanolamine salts such as monoethanolamine salt, diethanolamine salt, and triethanolamine salt, alkylamine salts such as monoethylamine salt, diethylamine salt, and triethylamine salt, and polyamine salts such as ethylenediamine salt and triethylenediamine salt.

[0019] Of these, the salts are preferably alkali metal salts, and Li salts, Na salts and K salts are more preferred, with Li salts being particularly preferred.

[0020] The degree of neutralization of the carboxyl group in the present polymer is not particularly limited, but is, for example, 50 mol% or more, for example, 60 mol% or more, for example, 70 mol% or more, for example, 80 mol% or more, for example, 90 mol% or more, for example, 95 mol% or more, or for example, 100 mol%. The range of the degree of neutralization is, for example, 50 mol% or more and 100 mol% or less, for example, 60 mol% or more and 100 mol% or less, for example, 70 mol% or more and 100 mol% or less, or for example, 80 mol% or more and 100 mol% or less.

[0021] The ratio of the mass of the structural unit derived from acrylic acid to the total mass of the non-crosslinking structural units in the present polymer is not particularly limited, but is, for example, 10% by mass or more. The ratio of the mass of the specific structural unit to the total mass of the non-crosslinking structural units corresponds to the ratio of the mass of the monomer from which the specific structural unit is derived to the total mass of the non-crosslinking monomer. Therefore, the ratio of the mass of the specific monomer to the total mass of the non-crosslinking monomer corresponds to the ratio of the mass of the specific structural unit derived from the specific monomer to the total mass of the non-crosslinking structural units. Hereinafter, the same interpretation is applied to the mass ratio of other structural units and monomers.

[0022] When the proportion in the polymer is 10% by mass or more, the fine particles can easily exhibit a suitable thickening property for thickening aqueous systems. The proportion can be appropriately set according to the use of the thickener and the desired thickening property, and is, for example, 15% by mass or more, for example, 20% by mass or more, for example, 30% by mass or more, for example, 35% by mass or more, for example, 40% by mass or more, for example, 45% by mass or more, for example, 50% by mass or more, for example, 55% by mass or more, for example, 60% by mass or more, for example, 65% by mass or more, for example, 70% by mass or more, for example, 75% by mass or more, for example, 80% by mass or more, for example, 85% by mass or more, for example, 90% by mass or more, for example, 95% by mass or more, or for example, 100% by mass.

[0023] (Other non-crosslinkable structural units (A)) The present polymer may further comprise another non-crosslinkable structural unit in addition to the structural unit derived from acrylic acid, such as a structural unit derived from one or more non-crosslinkable vinyl monomers selected from hydroxyl group-containing vinyl monomers that are vinyl monomers other than acrylic acid.

[0024] Examples of the hydroxyl group-containing vinyl monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and mono(meth)acrylic acid esters of polyalkylene glycols such as polyethylene glycol and polypropylene glycol. These compounds may be used alone or in combination of two or more. As the vinyl monomer other than acrylic acid, it is preferable to use a hydroxyl-containing vinyl monomer in combination.

[0025] The ratio of the total mass of the structural units to the total mass of the non-crosslinkable structural units in the polymer is not particularly limited, but is, for example, 1% by mass or more, for example, 5% by mass or more, for example, 10% by mass or more, for example, 15% by mass or more, for example, 20% by mass or more, for example, 25% by mass or more, for example, 30% by mass or more, for example, 35% by mass or more, for example, 40% by mass or more, for example, 45% by mass or more, for example, 50% by mass or more. The upper limit is, for example, 60% by mass or less, for example, 50% by mass or less, for example, 40% by mass or less, for example, 30% by mass or less. The range of such vinyl monomers can be set by appropriately combining these lower and upper limits, and is, for example, 10% by mass or more and 60% by mass or less, for example, 10% by mass or more and 50% by mass or less, for example, 10% by mass or more and 40% by mass or less, and for example, 10% by mass or more and 30% by mass or less.

[0026] (Other non-crosslinkable structural units (B)) The polymer may further include other structural units derived from styrenes, (meth)acrylonitrile compounds, maleimide compounds, and unsaturated acid anhydrides. One or more of these may be used in combination.

[0027] The styrenes include styrene and its derivatives. Specific examples of the compounds include styrene, α-methylstyrene, β-methylstyrene, vinylxylene, vinylnaphthalene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, pn-butylstyrene, p-isobutylstyrene, pt-butylstyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-chloromethylstyrene, p-chloromethylstyrene, o-chlorostyrene, p-chlorostyrene, o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, and divinylbenzene, and one or more of these can be used. Among these, from the viewpoint of polymerizability, styrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-hydroxystyrene, m-hydroxystyrene, and p-hydroxystyrene are preferred.

[0028] Examples of the (meth)acrylonitrile compound include (meth)acrylonitrile, α-methylacrylonitrile, etc. For example, acrylonitrile is used.

[0029] The maleimide compound includes maleimide and N-substituted maleimide compounds. Specific examples of the N-substituted maleimide compound include N-alkyl-substituted maleimide compounds such as N-methylmaleimide, N-ethylmaleimide, Nn-propylmaleimide, N-isopropylmaleimide, Nn-butylmaleimide, N-isobutylmaleimide, N-tert-butylmaleimide, N-pentylmaleimide, N-hexylmaleimide, N-heptylmaleimide, N-octylmaleimide, N-laurylmaleimide, and N-stearylmaleimide; N-cyclopentylmaleimide, N-cyclohexylmaleimide, and the like. N-cycloalkyl-substituted maleimide compounds such as N-phenylmaleimide, N-(4-hydroxyphenyl)maleimide, N-(4-acetylphenyl)maleimide, N-(4-methoxyphenyl)maleimide, N-(4-ethoxyphenyl)maleimide, N-(4-chlorophenyl)maleimide, and N-(4-bromophenyl)maleimide, and N-aralkyl-substituted maleimide compounds such as N-benzylmaleimide, can be used alone or in combination. For example, N-phenylmaleimide can be used.

[0030] Examples of the unsaturated acid anhydride include maleic anhydride, itaconic anhydride, citraconic anhydride, etc., and one or more of these can be used.

[0031] Among these, for example, it is preferable to include at least styrenes. This is because styrenes can easily undergo living radical polymerization as described later, and can impart moderate hydrophobicity and affinity to organic solvents. In addition, it is possible to impart hydrophobicity or affinity to organic solvents to the present polymer. In this way, for example, when polymer microparticles are produced by a dispersion polymerization method in a polar organic solvent as described later, the other structural units tend to be present on the surface layer of the present microparticles, improving the dispersion stability of the present microparticles.

[0032] The ratio of the mass of structural units derived from styrenes to the total mass of non-crosslinked structural units is not particularly limited, but is, for example, 0.5 mass% or more and 30 mass% or less, such as, for example, 0.5 mass% or more and 25 mass% or less, and such as, for example, 0.5 mass% or more and 10 mass% or less.

[0033] The (meth)acrylonitrile compound, the maleimide compound and the acid anhydride can be used alone, and it is preferable to use one or more of these three types in combination with styrenes. This is because all of these three types can maintain, adjust or impart hydrophobicity or organic solvent affinity to the first polymer described below. Among them, one or more of (meth)acrylonitrile compounds such as acrylonitrile, maleimide compounds such as N-phenylmaleimide and acid anhydrides are preferred, and combinations such as styrene and acrylonitrile, and styrene and N-phenylmaleimide are suitable.

[0034] (Other non-crosslinkable structural units (C)) The non-crosslinkable structural unit in the polymer may further include another structural unit (C) derived from another vinyl monomer, so long as it does not impair the intended function of the microparticle. Such vinyl monomers are not particularly limited, but include unsaturated carboxylic acids such as methacrylic acid, cinnamic acid, and crotonic acid, unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid, and monoalkyl esters of unsaturated dicarboxylic acids, and one or more of these may be used.

[0035] Further examples include (meth)acrylic acid alkyl esters, (meth)acrylic acid alkoxyalkyl esters, etc. The ratio of the mass of the other structural units to the total mass of the non-crosslinked structural units is, for example, 20 mass% or less, such as, for example, 10 mass% or less, such as, for example, 5 mass% or less, such as, for example, 3 mass% or less, or for example, 1 mass% or less.

[0036] Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, and (meth)acrylic acid. linear or branched alkyl ester compounds of (meth)acrylic acid, such as decyl (meth)acrylate and dodecyl (meth)acrylate; and aliphatic cyclic ester compounds of (meth)acrylic acid, such as cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentanyl (meth)acrylate.

[0037] Examples of the (meth)acrylic acid alkoxyalkyl ester include methoxymethyl (meth)acrylate, ethoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-propoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 3-propoxypropyl (meth)acrylate, 3-butoxypropyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 3-ethoxybutyl (meth)acrylate, 3-propoxybutyl (meth)acrylate, and 3-butoxybutyl (meth)acrylate.

[0038] Furthermore, the polymer may comprise a crosslinkable structural unit, the crosslinkable monomer from which the crosslinkable structural unit is derived being described below.

[0039] The present polymer can have a form including, for example, a polymer chain including a structural unit derived from acrylic acid or the structural unit and another structural unit A (preferably not including another structural unit B), and a polymer chain including another structural unit B. The present microparticles having such a form have a small average particle size and excellent dispersibility, and can exhibit high viscosity increase and transparency.

[0040] (Production of the Microparticles) The microparticles can be synthesized by known polymerization methods such as emulsion polymerization and dispersion polymerization, but it is preferable to obtain the polymer by dispersion polymerization. This is because dispersion polymerization can obtain the microparticles having excellent uniformity of average particle size. Hereinafter, a method for producing polymer microparticles suitable for obtaining the microparticles will be described.

[0041] (Method of manufacturing the microparticles) For example, in the presence of a first polymer having a first polymer chain containing the above-mentioned other structural unit (B) and a living radical polymerization active unit, at least acrylic acid is dispersed and polymerized by living radical polymerization based on the living radical polymerization active unit. This allows the present fine particles to be obtained as dispersed fine particles from the present polymer in which a second polymer chain having an acrylic acid-derived structural unit is bonded to the first polymer chain. According to this production method, the present fine particles can be obtained with a small average particle size. This is because the use of the first polymer allows the present polymer to be polymerized with excellent polymerization stability, and the generation of agglomerates during the polymerization process can be suppressed, and the generation of coarse particles can be suppressed.

[0042] (First polymer and its production method) The first polymer can have a first polymer chain containing another structural unit (B) in the present polymer, and a living radical polymerization active unit.

[0043] (First polymer chain) The first polymer chain can be obtained by polymerizing one or more vinyl monomers (hereinafter also referred to as the first monomer) selected from various monomers from which the other non-crosslinkable structural unit (B) described above is derived. The various modes of use of the vinyl monomers described above can also be applied to this production method.

[0044] The styrenes are, for example, 20% by mass or more of the total mass of the first monomer for polymerizing the first polymer chain. When the styrenes are 20% by mass or more, living radical polymerization becomes easy, and suitable hydrophobicity and affinity for organic solvents can be appropriately imparted. For example, the styrenes are 30% by mass or more, for example, 35% by mass or more, for example, 40% by mass or more, for example, 50% by mass or more, for example, 60% by mass or more, for example, 65% by mass or more, for example, 70% by mass or more, for example, 75% by mass or more. The styrenes are 100% by mass or less, for example, 95% by mass or less, for example, 90% by mass or less, for example, 85% by mass or less, for example, 80% by mass or less, for example, 75% by mass or less of the total mass. The range of the styrenes relative to the total mass can be set by appropriately combining the above-mentioned lower and upper limits, and is, for example, 20% by mass or more and 95% by mass or less, for example, 30% by mass or more and 75% by mass or less, and for example, 35% by mass or more and 85% by mass or less.

[0045] When used in combination with styrenes, the total amount of these one or more monomers other than styrenes is, for example, 20% by mass or more of the total mass of the first monomer. Also, for example, 25% by mass or more, for example, 30% by mass or more, for example, 35% by mass or more, for example, 40% by mass or more, for example, 50% by mass or more, for example, 60% by mass or more. Also, the (meth)acrylonitrile compound is 80% by mass or less, for example, 75% by mass or less, for example, 70% by mass or less, for example, 65% by mass or less, for example, 60% by mass or less, for example, 55% by mass or less, for example, 50% by mass or less of the total mass. The total amount of these one or more first monomers other than styrenes can be set by appropriately combining the above-mentioned lower and upper limits, and is, for example, 20% by mass or more and 65% by mass or less, and also, for example, 25% by mass or more and 50% by mass or less.

[0046] The first polymer chain may be a polymer chain of only the first monomer described above, but if necessary, other vinyl monomers other than the above can be used as the first monomer. For example, known vinyl monomers such as unsaturated carboxylic acids and their alkyl esters, unsaturated dicarboxylic acids such as itaconic acid, maleic acid, and fumaric acid, and monoalkyl esters of unsaturated dicarboxylic acids can be used. The amount of such other monomers is, for example, 10% by mass or less, for example, 5% by mass or less, for example, 3% by mass or less, for example, 1% by mass or less, and for example, 0.5% by mass or less of the total mass of the monomers constituting the first polymer chain. These monomers are monomers from which the non-crosslinkable structural unit (C) described above is derived, in addition to the acrylic acid-derived structural unit in the present microparticles.

[0047] In addition, the first polymer may have a polymer chain as another block in addition to the first polymer chain. Examples of the vinyl monomer constituting such a polymer chain include (meth)acrylic acid and known (meth)acrylic acid hydroxyalkyl esters. Examples of such (meth)acrylic acid hydroxyalkyl esters include various compounds already exemplified. Such other polymer chains are directly linked to the living radical polymerization active unit described later and are provided so as to be linked to the first polymer chain, so that a part of the second monomer used in the polymer microparticles can be provided in advance in the first polymer. Such polymer chains of other blocks can be provided in an amount of, for example, 10 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of the first polymer chain. These monomers are monomers from which the non-crosslinkable structural unit (C) described above in the present microparticles is derived.

[0048] (Living radical polymerization active unit) The first polymer can have a living radical polymerization active unit. Living radical polymerization is generally considered to be a polymerization reaction that consists of only an initiation reaction and a propagation reaction in the polymerization process, does not involve side reactions that deactivate the propagation end, such as a chain transfer reaction or a termination reaction, and the propagation end always maintains propagation activity based on radical species (living radical polymerization activity) during polymerization. The living radical polymerization active unit is a propagation active unit in living radical polymerization. The living radical polymerization active unit is also a unit derived from a control agent for the living radical polymerization method.

[0049] There are various known living radical polymerizations based on their reaction mechanisms, and the living radical polymerization active unit can be an active unit in living radical polymerization by chain exchange mechanism or bond-dissociation mechanism. These living radical polymerizations can easily produce a first polymer with a narrow molecular weight distribution, and in dispersion polymerization of polymer fine particles, various monomers can be selected for the solubility of the first polymer in the polymerization solvent and for the function as a dispersion stabilizer.

[0050] Examples of living radical polymerization by exchange chain mechanism include reversible addition-fragmentation chain transfer polymerization (RAFT), iodine transfer polymerization, polymerization using an organotellurium compound (TERP), polymerization using an organoantimony compound (SBRP), and polymerization using an organobismuth compound (BIRP). Living radical polymerization by exchange chain mechanism is preferred in that it can reduce the average particle size of the polymer particles. Among these, the RAFT and iodine transfer polymerization are preferred in that they can narrow the molecular weight distribution of the first polymer. Furthermore, the RAFT method is preferably used.

[0051] An example of living radical polymerization based on a bond-dissociation mechanism is the nitroxy radical method (NMP method).

[0052] The polymerization conditions for these various living radical polymerizations are well known to those skilled in the art, and the synthesis of the first polymer by the RAFT method, the iodine transfer polymerization method, and the NMP method will be exemplified as necessary. Note that, although the living radical polymerization process includes various processes such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization, in consideration of being the polymerization base point in the production of polymer microparticles and functioning as a dispersion stabilizer, for example, solution polymerization can be used in the production of the first polymer.

[0053] The first polymer can be synthesized by the RAFT method using, for example, a control agent for the RAFT method. The RAFT method is a living radical polymerization method suitable for obtaining a first polymer having a molecular weight distribution of 2.0 or less. The control agent for living radical polymerization in the RAFT method (RAFT agent) is not particularly limited, and a known RAFT agent can be used. For example, dithioester compounds, xanthate compounds, trithiocarbonate compounds, and dithiocarbamate compounds can be mentioned. The RAFT agent may be a monofunctional agent having one active site, or a bifunctional or higher functional agent having two or more active sites can be used. A bifunctional or higher functional RAFT agent is one in which the polymer chain extends in two or more directions. From the viewpoint of producing polymer microparticles, it may be preferable to use a bifunctional or trifunctional or higher functional RAFT agent.

[0054] The substituent in the RAFT agent can be appropriately determined in consideration of the monomer from which the structural unit (B) is derived and the monomer that polymerizes the second polymer chain described below. The amount of the RAFT agent used is appropriately adjusted depending on the target Mn, and can be, for example, 0.1 parts by mass or more and 10 parts by mass or less, or, for example, 0.5 parts by mass or more and 5 parts by mass or less, or, for example, 1 part by mass or more and 4 parts by mass or less, or, for example, 1 part by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the first monomer.

[0055] As the RAFT agent, various known RAFT agents can be used, such as dithioester compounds, xanthate compounds, trithiocarbonate compounds, and dithiocarbamate compounds. More specifically, examples of the RAFT agents include dibenzyl trithiocarbonate, dithiobenzoate 2-cyano-2-propyl benzodithioate, 2-phenyl-2-propyl benzodithioate, trithiocarbonate, 2-cyano-2-propyl dodecyl trithiocarbonate, 2-(dodecylthiocarbonothioylthio)-2-methyl methyl propanoate, distyryl trithiocarbonate, dicumyl trithiocarbonate, dithiocarbamate, and cyanomethyl N-methyl-N-phenyl dithiocarbamate.

[0056] As the radical polymerization initiator (radical generator) used in polymerization by the RAFT method, known radical polymerization initiators such as azo compounds, organic peroxides and persulfates can be used, but azo compounds are preferred because they are safe and easy to handle and do not easily cause side reactions during radical polymerization. Specific examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), dimethyl-2,2'-azobis(2-methylpropionate), and 2,2'-azobis(2-methylbutyronitrile). The radical polymerization initiators can be used alone or in combination.

[0057] The proportion of such radical polymerization initiator used is not particularly limited, but from the viewpoint of obtaining a polymer with a narrower molecular weight distribution, the proportion of radical polymerization initiator used can be, for example, 0.005 mass% or more and 2 mass% or less, or for example, 0.005 mass% or more and 1 mass% or less, or for example, 0.005 mass% or more and 0.5 mass% or less, relative to 100 mass parts of the total mass of the first vinyl monomer.

[0058] The RAFT method may be carried out in the presence of a chain transfer agent, if necessary. As the chain transfer agent, one or more known chain transfer agents can be used.

[0059] In addition, in the RAFT method, known polymerization solvents can be used, and examples thereof include nitrile solvents, aromatic solvents, ketone solvents, ester solvents, orthoester solvents, dimethylformamide, dimethylsulfoxide, alcohol, and water. Specific examples of nitrile solvents include acetonitrile, isobutyronitrile, and benzonitrile. Specific examples of aromatic solvents include benzene, toluene, xylene, and anisole. Specific examples of ketone solvents include acetone, methyl ethyl ketone, and methyl isobutyl ketone. Specific examples of ester solvents include methyl acetate, ethyl acetate, propyl acetate, and butyl acetate. Specific examples of orthoester solvents include trimethyl orthoformate, triethyl orthoformate, tri(n-propyl) orthoformate, tri(isopropyl) orthoformate, trimethyl orthoacetate, triethyl orthoacetate, triethyl orthopropionate, trimethyl ortho-n-butyrate, and trimethyl orthoisobutyrate. Preferably, a nitrile solvent such as acetonitrile and / or an aromatic solvent such as anisole can be used.

[0060] The concentration when polymerizing the first polymer by living radical polymerization is not particularly limited relative to the total mass of the polymerization solvent, the first monomer, etc., charged, but can be, for example, 10% by mass or more and 80% by mass or less, or, for example, 15% by mass or more and 70% by mass or less, or 20% by mass or more and 70% by mass or less, etc.

[0061] The reaction temperature during the polymerization reaction by the RAFT method is preferably 40° C. or higher and 100° C. or lower, more preferably 45° C. or higher and 90° C. or lower, and even more preferably 50° C. or higher and 80° C. or lower. If the reaction temperature is 40° C. or higher, the polymerization reaction can proceed smoothly. On the other hand, if the reaction temperature is 100° C. or lower, side reactions can be suppressed and restrictions on usable initiators and solvents can be relaxed.

[0062] The first polymer can also be synthesized by iodine transfer polymerization using a control agent for iodine transfer polymerization. The control agent for iodine transfer polymerization is not particularly limited, and known control agents can be used, such as methyl iodide, methylene iodide, iodoform, carbon tetraiodide, 1-phenylethyl iodide, benzyl iodide, methyl 2-iodoisobutyrate, ethyl 2-iodoisobutyrate, ethyl 2-iodo-2-phenylacetate, ethylene glycol bis(2-iodo-2-phenylacetate), and ethylene glycol bis(2-iodoisobutyrate).

[0063] The amount of the inhibitor for the iodine transfer reaction is appropriately adjusted according to the target Mn, but can be, for example, 0.1 to 10 parts by mass, or 0.5 to 5 parts by mass, or 1 to 4 parts by mass, relative to 100 parts by mass of the first monomer. For example, 0.1 to 10 parts by mass, or 0.5 to 5 parts by mass, or 1 to 4 parts by mass, relative to 100 parts by mass of the first monomer.

[0064] As the radical polymerization initiator (radical generator) used in polymerization by the iodine transfer polymerization method, known radical polymerization initiators such as azo compounds, organic peroxides, and persulfates can be used in the same manner and amount as in the RAFT method. The reaction temperature, polymerization solvent, and first monomer concentration in the iodine transfer polymerization method can be appropriately selected from the same manner as in the RAFT method.

[0065] The first polymer can also be synthesized by the NMP method using a control agent for the NMP method. The control agent in the NMP method is not particularly limited, and known control agents can be used, such as 2,2,6,6-tetramethylpiperidinyl-1-oxyl (TEMPO), N-tert-butyl-N-[1-diethylphosphono-(2,2-dimethylpropyl)]nitroxide (DEPN), 2,2,5-trimethyl-4-phenyl-3-azahexane-3-nitroxide (TIPNO), N-tert-butyl-N-(1-tert-butyl-2-ethylsulfinyl)propyl-N-oxyl (BESN), etc.

[0066] The amount of the inhibitor used in the NMP method is appropriately adjusted depending on the target Mn, but for example, 0.1 parts by mass to 10 parts by mass, for example, 0.5 parts by mass to 5 parts by mass, or for example, 1 part by mass to 4 parts by mass, can be used relative to 100 parts by mass of the first monomer. For example, 0.1 parts by mass to 10 parts by mass, for example, 0.5 parts by mass to 5 parts by mass, or for example, 1 part by mass to 4 parts by mass, can be used relative to 100 parts by mass of the first monomer.

[0067] As the radical polymerization initiator (radical generator) used in the polymerization by the NMP method, known radical polymerization initiators such as azo compounds, organic peroxides, and persulfates can be used in the same manner and amount as in the RAFT method. The reaction temperature, polymerization solvent, and first monomer concentration in the NMP method can be appropriately selected from the same manner as in the RAFT method.

[0068] By synthesizing a first polymer by a predetermined living radical polymerization, a first polymer having a first polymer chain containing a first monomer and a living polymerization active unit can be obtained. The first polymer can also have two or more types of first polymer chains. For example, by carrying out living radical polymerization or the like using one or more types of first monomers of a certain composition, and then carrying out living radical polymerization or the like using one or more types of first monomers of another composition, a first polymer having a first polymer chain (block) having a unit derived from a first monomer of a different composition can be obtained.

[0069] The first polymer may also have a block (another polymer chain) different from the first polymer chain. In this case, a radical polymerization initiator and another vinyl monomer may be continuously or newly supplied to the first polymer having the first polymer chain to obtain a first polymer having another polymer chain (block) composed of units derived from a monomer other than the first monomer and having a different composition from the first polymer chain.

[0070] According to a specific living radical polymerization, a first polymer having a controlled number average molecular weight (Mn) and weight average molecular weight (Mw) can be obtained. The Mn of the first polymer is not particularly limited, but is, for example, 3,000 or more, for example, 5,000 or more, for example, 7,000 or more, for example, 8,000 or more, or for example, 10,000 or more. The Mn is 50,000 or less, for example, 30,000 or less, for example, 25,000 or less, for example, 20,000 or less, for example, 15,000 or less, for example, 14,000 or less, or for example, 12,000 or less. The range of Mn can be set by appropriately combining the above-mentioned lower and upper limits, and is, for example, 5,000 or more and 25,000 or less, for example, 10,000 or more and 25,000 or less, for example, 10,000 or more and 15,000 or less, and for example, 10,000 or more and 14,000 or less.

[0071] The Mw of the first polymer is not particularly limited, but is, for example, 5,000 or more, for example, 7,000 or more, for example, 9,000 or more, for example, 10,000 or more, for example, 13,000 or more, or for example, 15,000 or more. The Mw is also, for example, 60,000 or less, for example, 55,000 or less, for example, 50,000 or less, for example, 45,000 or less, for example, 40,000 or less, for example, 36,000 or less, for example, 35,000 or less, for example, 30,000 or less, or for example, 25,000 or less. The Mw range can be set by appropriately combining the above-mentioned lower and upper limits, and is, for example, 1,000 or more and 40,000 or less, for example, 10,000 or more and 35,000 or less, for example, 10,000 or more and 30,000 or less, and for example, 15,000 or more and 25,000 or less.

[0072] The Mw and Mn of the first polymer can be measured by gel permeation chromatography using polystyrene as a standard substance. The detailed chromatography conditions can be those disclosed in the examples below.

[0073] The molecular weight distribution (Mw / Mn) of the first polymer is not particularly limited, but may be, for example, 2.5 or less, for example, 2.4 or less, for example, 2.3 or less, for example, 2.0 or less, for example, 1.6 or less, for example, 1.5 or less, for example, 1.4 or less, or for example, 1.3 or less. The molecular weight distribution may be, for example, 1.1 or more, for example, 1.2 or more, for example, 1.3 or more, for example, 1.4 or more, or for example, 1.5 or more. The range of the molecular weight distribution may be set by appropriately combining the above-mentioned lower and upper limits, and may be, for example, 1.1 or more and 2.5 or less, for example, 1.1 or more and 2.4 or less, for example, 1.1 or more and 2.3 or less, or for example, 1.1 or more and 2.0 or less.

[0074] The narrower the molecular weight distribution, the smaller the average particle size of the resulting polymer microparticles tends to be. To obtain polymer microparticles with an average particle size of 0.2 μm or less, the molecular weight distribution is preferably 2.4 or less, and to obtain polymer microparticles with an even smaller average particle size, the molecular weight distribution is preferably 1.7 or less, more preferably 1.6 or less, and even more preferably 1.4 or less.

[0075] The first polymer can have a first polymer chain and a living polymerization active unit, but typically, when a monofunctional control agent is used, the first polymer chain has a living polymerization active unit at its end, and when a bifunctional or higher-functional control agent is used, the first polymer chain is branched in two or more directions from the living polymerization active unit, each of which has a first polymer chain. In either embodiment, when another polymer chain is provided, the other polymer chain is directly bonded to the living polymerization active unit, and the first polymer chain is bonded to the distal end of the other polymer chain so that the first polymer chain is provided on the more distal side of the living polymerization active unit.

[0076] (Production process of polymer microparticles) In the presence of a first polymer, one or more monomers including at least acrylic acid (hereinafter also referred to as a second monomer) can be polymerized by dispersion polymerization using living radical polymerization based on living radical polymerization active units, to produce polymer microparticles. In this method, a second polymer chain is generated and provided by polymerizing a second monomer to the living radical polymerization active units of the first polymer, thereby synthesizing a present polymer having a first polymer chain and a second polymer chain, and the present microparticles can be produced from the present polymer.

[0077] In this method, the first polymer can be used as a polymerization base point for acrylic acid during the production of polymer microparticles, and can also be used as a dispersion stabilizer for the polymer microparticles in the polymerization solvent. This makes it possible to obtain polymer microparticles with a small average particle size and a narrow average particle size distribution by suppressing polymerization stability, i.e., by suppressing aggregation of polymer microparticles during the polymerization process and suppressing the generation of coarse aggregated particles.

[0078] In producing polymer microparticles by polymerizing the second monomer in the presence of the first polymer, in order to make the first polymer function as a dispersion stabilizer, for example, the first polymer can be used in an amount of 0.3 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the total mass of the second monomer. By using the first polymer in such a range, it is possible to produce polymer microparticles mainly containing the second monomer while making the first polymer function as a dispersion stabilizer. In addition, if the first polymer is less than 0.3 parts by mass, it is difficult to obtain a sufficient dispersion stabilizing effect, and the average particle diameter of the polymer microparticles is likely to exceed 0.2 μm, and even if it exceeds 50 parts by mass, the functionality as a dispersion stabilizer is difficult to improve, and the effect of decreasing the average particle diameter of the polymer microparticles is also small. Note that the first polymer referred to here corresponds to a polymer chain having living radical polymerization activity (the first polymer chain and the living radical polymerization active unit) in this polymer.

[0079] The first polymer can be used in an amount of, for example, 0.5 parts by mass or more, or, for example, 1 part by mass or more, relative to 100 parts by mass of the total mass of the second monomer. The first polymer can be used in an amount of, for example, 50 parts by mass or less, or, for example, 40 parts by mass or less, or, for example, 30 parts by mass or less, or, for example, 20 parts by mass or less. The range of the amount of the first polymer used relative to 100 parts by mass of the total mass of the second monomer can be set by appropriately combining the above upper and lower limits, and is, for example, 0.3 parts by mass or more and 30 parts by mass or less, for example, 0.3 parts by mass or more and 20 parts by mass or less, for example, 0.5 parts by mass or more and 20 parts by mass or less, or, for example, 1 part by mass or more and 20 parts by mass or less.

[0080] The second monomer may be acrylic acid or one or more monomers selected from the monomers derived from the above-mentioned structural unit A. The carboxyl group in acrylic acid or the like may be in the form of a salt as described above for acrylic acid.

[0081] The content of acrylic acid in the second monomer can be, for example, 30% by mass or more, for example, 40% by mass or more, for example, 50% by mass or more, for example, 60% by mass or more, for example, 70% by mass or more, for example, 80% by mass or more, for example, 90% by mass or more, for example, 95% by mass or more, or for example, 100% by mass, based on the total mass of the second monomer. The range of acrylic acid used relative to the total mass of the second monomer can be set by appropriately combining the above-mentioned lower and upper limits, and is, for example, 60% by mass or more and 100% by mass or less, for example, 80% by mass or more and 100% by mass or less, and for example, 90% by mass or more and 100% by mass or less.

[0082] The mass ratio of the hydroxyl group-containing vinyl monomer to the total mass of the second monomer is, for example, 5% by mass or more, for example, 10% by mass or more, for example, 20% by mass or more, for example, 30% by mass or more, or for example, 40% by mass or more. It is also 50% by mass or less, for example, 40% by mass or less, for example, 30% by mass or less, for example, 20% by mass or less, for example, 10% by mass or less, or for example, 5% by mass or less. The range of the hydroxyl group-containing vinyl monomer to the total mass of the second monomer can be set by appropriately combining the above-mentioned lower and upper limits, and is, for example, 0% by mass or more and 40% by mass or less, for example, 0% by mass or more and 20% by mass or less, or for example, 0% by mass or more and 10% by mass or less.

[0083] The second monomer may contain other vinyl monomers as long as they do not impair the intended function of the microparticles. Such vinyl monomers may be one or more selected from the monomers from which the structural unit (C) described above is derived. Such second monomers may be contained, for example, in an amount of 20% by mass or less, for example, 10% by mass or less, for example, 5% by mass or less, for example, 3% by mass or less, or for example, 1% by mass or less, based on the total mass of the second monomers.

[0084] In the process for producing the polymer microparticles, a crosslinked structure can be introduced into the second polymer chains.

[0085] The method for introducing the crosslinked structure is not particularly limited, and examples thereof include the following methods. 1) Copolymerization of crosslinkable monomers 2) Utilizing chain transfer to polymer chains during radical polymerization 3) After synthesizing a polymer having a reactive functional group, a crosslinking agent is added as necessary to perform post-crosslinking. Among these, the method of copolymerizing a crosslinkable monomer is preferred because the operation is simple and the degree of crosslinking can be easily controlled.

[0086] Examples of the crosslinkable monomer include a polyfunctional polymerizable monomer having two or more polymerizable unsaturated groups, and a monomer having a self-crosslinkable crosslinkable functional group such as a hydrolyzable silyl group. The polyfunctional polymerizable monomer is a compound having two or more polymerizable functional groups such as a (meth)acryloyl group and an alkenyl group in the molecule, and examples of the polyfunctional polymerizable monomer include a polyfunctional (meth)acrylate compound, a polyfunctional alkenyl compound, and a compound having both a (meth)acryloyl group and an alkenyl group. These compounds may be used alone or in combination of two or more. Among these, a polyfunctional alkenyl compound is preferred in that it is easy to obtain a uniform crosslinked structure, and a polyfunctional allyl ether compound having a plurality of allyl ether groups in the molecule is particularly preferred.

[0087] Examples of the polyfunctional (meth)acrylate compound include di(meth)acrylates of dihydric alcohols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate; tri(meth)acrylates of trihydric or higher polyhydric alcohols such as trimethylolpropane tri(meth)acrylate, tri(meth)acrylate of an ethylene oxide modified trimethylolpropane, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and poly(meth)acrylates such as tetra(meth)acrylate; and bisamides such as methylene bisacrylamide and hydroxyethylene bisacrylamide.

[0088] Examples of polyfunctional alkenyl compounds include polyfunctional allyl ether compounds such as trimethylolpropane diallyl ether, trimethylolpropane triallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, tetraallyloxyethane, and polyallylsucrose; polyfunctional allyl compounds such as diallyl phthalate; and polyfunctional vinyl compounds such as divinylbenzene.

[0089] Examples of compounds having both a (meth)acryloyl group and an alkenyl group include allyl (meth)acrylate, isopropenyl (meth)acrylate, butenyl (meth)acrylate, pentenyl (meth)acrylate, and 2-(2-vinyloxyethoxy)ethyl (meth)acrylate.

[0090] Specific examples of the monomer having a self-crosslinkable crosslinkable functional group include a hydrolyzable silyl group-containing vinyl monomer, N-methylol (meth)acrylamide, N-methoxyalkyl (meth)acrylamide, etc. These compounds may be used alone or in combination of two or more.

[0091] The hydrolyzable silyl group-containing vinyl monomer is not particularly limited as long as it is a vinyl monomer having at least one hydrolyzable silyl group. For example, vinyltrimethoxysilane, Examples of the vinyl silanes include vinyl triethoxysilane, vinyl methyl dimethoxy silane, vinyl dimethyl methoxy silane, and the like; silyl group-containing acrylic esters, such as trimethoxy silyl propyl acrylate, triethoxy silyl propyl acrylate, methyl dimethoxy silyl propyl acrylate, and the like; silyl group-containing methacrylic esters, such as trimethoxy silyl propyl methacrylate, triethoxy silyl propyl methacrylate, methyl dimethoxy silyl propyl methacrylate, dimethyl methoxy silyl propyl methacrylate, and the like; silyl group-containing vinyl ethers, such as trimethoxy silyl propyl vinyl ether; and silyl group-containing vinyl esters, such as vinyl trimethoxy silyl undecanoate, and the like.

[0092] The amount of the crosslinkable monomer used is, for example, 0.1% by mass or more and 5% by mass or less, for example, 0.5% by mass or more and 3% by mass or less, based on the total mass of monomers other than the crosslinkable monomer (non-crosslinkable monomers). The amount of the crosslinkable monomer used is, for example, 0.01% by mol or more and 2% by mol or less, for example, 0.03% by mol or more and 2% by mol or less, for example, 0.5% by mol or more and 1% by mol or less, based on the total molar amount of the non-crosslinkable monomers.

[0093] In producing polymer microparticles, since the first polymer has a living radical polymerization active unit, the second monomer is polymerized to the living polymerization active unit by adding an appropriate radical polymerization initiator (radical generator). The radical polymerization initiator can be appropriately selected from the various aspects described for the RAFT agent. The proportion of the radical polymerization initiator used is not particularly limited, but from the viewpoint of obtaining a polymer with a narrower molecular weight distribution, it can be used in an amount of, for example, 0.01% by mass or more and 5% by mass or less, or, for example, 0.02% by mass or more and 3% by mass or less, or, for example, 0.03% by mass or more and 3% by mass or less, relative to 100 parts by mass of the total mass of the second monomer.

[0094] The production of polymer microparticles can be carried out by known polymerization methods, but is not particularly limited thereto, and is preferably carried out by dispersion polymerization. By adopting the dispersion polymerization method, polymer microparticles having a small average particle size can be easily obtained. The polymerization solvent used in the production of polymer microparticles can be appropriately set according to the polymerization method adopted and the types of the first vinyl monomer, the second monomer, etc. When the dispersion polymerization method is adopted, for example, various solvents used in the synthesis of the first polymer can be appropriately used. For example, a nitrile solvent such as acetonitrile can be used.

[0095] By using the polymerization solvent used in the synthesis of the first polymer, the first polymer can be dissolved and the solvent is a good solvent that easily dissolves the first polymer chains and the inhibitor for living radical polymerization, so that the first polymer chains are present on the surface side of the polymer microparticles and the second polymer chains made of acrylic acid or the like that become the extension ends are present inside the polymer microparticles while being organized during polymerization. This makes it easier to form a microparticle structure with excellent dispersion stability.

[0096] The polymerization solvent used in producing polymer microparticles can further be determined taking into account dispersion polymerization, and must be a poor solvent that dissolves the second monomer, etc., but does not dissolve the polymer microparticles containing the polymer chains.

[0097] For example, examples of polymerization solvents used in the production of polymer microparticles include nitrile-based solvents such as acetonitrile, alcohol-based solvents such as methanol and t-butyl alcohol, ketone-based solvents such as acetone, furan-based solvents such as tetrahydrofuran, ether-based solvents such as tetrahydrofuran, as well as benzene, ethyl acetate, dichloroethane, n-hexane, cyclohexane, and n-heptane, and these can be used alone or in combination of two or more. Furthermore, these solvents can also be used as mixed solvents with highly polar solvents such as water. When the polymerization solvent for the polymer microparticles contains a highly polar solvent such as water, (meth)acrylic acid can be quickly neutralized in the polymerization step. The amount of the highly polar solvent used is preferably 0.05 to 10.0% by mass, more preferably 0.1 to 5.0% by mass, and even more preferably 0.1 to 1.0% by mass based on the total mass of the medium. If the proportion of the highly polar solvent is 0.05% by mass or more, an effect on the neutralization reaction is observed, and if it is 10.0% by mass or less, no adverse effect on the polymerization reaction is observed.

[0098] In the polymerization step, organic acids, organic acid salts, organic bases, etc. having a chelating or coordinating ability with metal ions, such as tartaric acid, citric acid, lactic acid, glycolic acid, malic acid, salicylic acid, fumaric acid, methanesulfonic acid, maleic acid, acetic acid, disodium EDTA, urea, triethylamine, and ammonia, as well as inorganic acids, such as hydrochloric acid, phosphoric acid, sulfuric acid, nitric acid, and hydrobromic acid, can be used in combination as a rate regulator for the crosslinking reaction.

[0099] The concentration of the second monomer in the total mass of the polymerization charge including the polymerization solvent, the first polymer, the monomer, etc. is not particularly limited and can be set appropriately, for example, from 5% by mass to 30% by mass, and can also be, for example, from 10% by mass to 20% by mass.

[0100] The reaction temperature during the polymerization reaction in the production of the multi-component fine particles is not particularly limited, but is, for example, 40°C or higher and 100°C or lower. Also, for example, it is 45°C or higher and 90°C or lower, and also, for example, it is 50°C or higher and 80°C or lower. If the reaction temperature is 40°C or higher, the polymerization reaction can proceed smoothly. On the other hand, if the reaction temperature is 100°C or lower, side reactions can be suppressed and restrictions on the initiator and solvent that can be used are relaxed.

[0101] In the production of the present microparticles, a neutralization step can be provided as appropriate.Typically, a basic compound containing a base such as lithium hydroxide, which is used for neutralizing the carboxyl group of the present polymer, is added to the polymerization reaction solution of the present microparticles in an amount that achieves the intended degree of neutralization, and the mixture is stirred at room temperature for example for several hours to several tens of hours to obtain a dispersion of the present microparticles that has been neutralized.

[0102] After the polymerization reaction, the particles are neutralized as necessary, washed several times, and then recovered by precipitation or the like, and dried to obtain the particles as a powder.

[0103] (The microparticles and their average particle size) The microparticles obtained by the present manufacturing method can have an embodiment having a first polymer chain, a second polymer chain, and a living radical polymerization active unit. The microparticles can have an average particle diameter of 0.01 μm or more and 0.20 μm or less. When the average particle diameter is 0.20 μm or less, it can be used as a thickener having both excellent aqueous solution thickening properties and transparency. When the average particle diameter exceeds 0.20 μm, neither thickening properties nor transparency are exhibited. From the viewpoint of thickening properties and transparency, for example, the average particle diameter is 0.01 μm or more and 0.15 μm or less, and for example, the average particle diameter is 0.01 μm or more and 0.10 μm or less.

[0104] The average particle size of the microparticles can be measured by measuring the particle sizes of the polymer microparticles observed under a microscope using image analysis software or the like, and calculating the average value. The average particle size of 400 particles in an image observed under a field emission scanning electron microscope can be taken as the average particle size of the microparticles. More specifically, the following method can be used.

[0105] Using a field emission scanning electron microscope (FE-SEM, JSM-6330F manufactured by JEOL Ltd.) or a microscope with a resolution equivalent to that of the electron microscope, multiple images in which 50 to 100 particles can be observed per image are obtained, and for the obtained images, using image analysis software "WinROOF" manufactured by Mitani Shoji Co., Ltd. or software capable of counting the number of particles and particle diameter with the same accuracy and precision as that software, the number of particles is counted until a total of 200 particles are counted, and the particle diameter (circle equivalent diameter) of the 200 particles is measured. Furthermore, this operation is repeated for another image, and the particle diameter of 200 particles is measured in the same manner. The average value of the particle diameters of these 400 particles in total can be regarded as the average particle diameter.

[0106] In addition, the microparticles can have a viscosity increasing property such that the viscosity of a 1.2% by mass aqueous solution is 5,000 mPa·s or more. When the viscosity is 5,000 mPa·s or more, It is extremely useful as an aqueous thickener. For example, the viscosity is 10,000 mPa·s or more, for example, 15,000 mPa·s or more, for example, 20,000 mPa·s or more, for example, 25,000 mPa·s or more, for example, 30,000 mPa·s or more, for example, 35,000 mPa·s or more, or for example, 40,000 mPa·s or more. The upper limit of the viscosity is not particularly limited, but is, for example, 60,000 mPa·s or less, for example, 50,000 mPa·s or less.

[0107] The thickening property can be measured by the following method. Ion-exchanged water is weighed into a 50cc container so that the microparticles are at a concentration of 1.2% by mass, and the container is set in a rotation / revolution type mixer (Thinky Corporation, Awatori Rentaro AR-250 or equivalent), and then the container is stirred (rotation speed 2000 rpm / revolution speed 800 rpm, 7 minutes), and further degassed (rotation speed 2200 rpm / revolution speed 60 rpm, 1 minute) to produce a hydrogel in which the microparticles are swollen in water, which is used as a sample. The temperature of this is kept at 25°C for 30 minutes, and the viscosity after 90 seconds at 12 rpm using a B-type viscometer is taken as the aqueous solution viscosity.

[0108] In addition, the microparticles can have a transparency in which, for example, the haze value of a 1.2% by mass aqueous solution is 50% or less. A haze value of 50% or less is excellent because it does not impair the appearance of the thickened product. The haze value is, for example, 40% or less, for example, 35% or less, for example, 30% or less, for example, 25% or less, for example, 20% or less, for example, 15% or less, or for example, 10% or less.

[0109] The transparency can be measured by the following method. A haze meter (device name NDH-2000, manufactured by Nippon Denshoku Industries Co., Ltd., or its equivalent) is used to measure the haze value (scattered light / total light transmission x 100 (%)) of a 1.2% by mass aqueous solution. The total light transmittance of water is taken as 100%. EXAMPLES

[0110] In the following, examples are described as specific examples to more specifically explain the disclosure of this specification. The following examples are for explaining the disclosure of this specification, and are not intended to limit the scope thereof. In the following examples, % represents mass %, and parts represents mass parts, unless otherwise specified.

[0111] (Method of measuring molecular weight of polymer) In the following examples, the molecular weight of the polymer was measured by gel permeation chromatography (GPC). That is, the number average molecular weight (Mn) and weight average molecular weight (Mw) were obtained based on polystyrene standards by THF-based GPC. The molecular weight distribution (Mw / Mn) was calculated from the obtained values. GPC was performed under the following conditions.

[0112] Column: Tosoh TSKgel SuperMultiporeHZ-M x 4 Solvent: Tetrahydrofuran Temperature: 40°C Detector: RI Flow rate: 600 μL / min

[0113] (Synthesis of polymer (first polymer) having living polymerization activity) (Polymer 1:P(St / PhMI)) In a 1L flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 2.0 parts of a RAFT agent (dibenzyl trithiocarbonate: hereinafter also referred to as "DBTTC"), 0.014 parts of 2,2'-azobis(2-methylbutyronitrile) (manufactured by Japan Finechem Co., Ltd., trade name "ABN-E": hereinafter also referred to as "ABN-E"), 38 parts of styrene (hereinafter also referred to as "St"), 62 parts of N-phenylmaleimide (hereinafter also referred to as "PhMI"), and 222 parts of acetonitrile were charged, thoroughly degassed by nitrogen bubbling, and polymerization was started in a thermostatic bath at 70 ° C. After 4 hours, the reaction was stopped by cooling to room temperature. The above polymerization solution was reprecipitated from methanol / water = 90 / 10 (vol%) and vacuum dried to obtain polymer 1. As a result of analysis by gas chromatography, the reaction rate of the obtained polymer 1 was St 75% and PhMI 75%. The molecular weight of polymer 1 was Mn 10,200, Mw 15,300, and Mw / Mn 1.51. St and PhMI correspond to the first monomer. The composition and molecular weight distribution of the polymer are shown in Table 1 (hereinafter the same).

[0114] (Polymer 2:P(St / AN)) A 1L flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube was charged with 2.0 parts of RAFT agent (DBTTC), 0.41 parts of ABN-E, 75 parts of St, 25 parts of acrylonitrile (hereinafter also referred to as "AN") and 67 parts of anisole, which were thoroughly degassed by nitrogen bubbling, and polymerization was started in a thermostatic bath at 80 ° C. After 4 hours, the reaction was stopped by cooling to room temperature. The above polymerization solution was purified by reprecipitation from methanol / water = 90 / 10 (vol%) and vacuum dried to obtain polymer 2. As a result of analysis by gas chromatography, the reaction rate of polymer 2 was St 73% and AN 72%. The molecular weight of polymer 2 was Mn 11,900, Mw 15,500, and Mw / Mn 1.30. St and AN correspond to the first monomer.

[0115] (Polymer 3: P(St / maleic anhydride)) A 1L flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube was charged with 2.0 parts of a RAFT agent (DBTTC), 0.070 parts of ABN-E, 52 parts of St, 48 parts of maleic anhydride and 207 parts of acetonitrile, which were thoroughly degassed by nitrogen bubbling, and polymerization was started in a thermostatic bath at 70 ° C. After 4 hours, the reaction was stopped by cooling to room temperature. The above polymerization solution was purified by reprecipitation from toluene and vacuum dried to obtain polymer 3. As a result of analysis by gas chromatography, the reaction rate of the obtained polymer 3 was St 71% and maleic anhydride 71%. The molecular weight of polymer 3 was Mn 13,800, Mw 22,200, and Mw / Mn 1.61. St and maleic anhydride correspond to the first monomer.

[0116] (Polymer 4:P(St / PhMI)) In a 1L flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 3.24 parts of 1-phenylethyl iodide (1-PEI), 0.019 parts of ABN-E, 38 parts of St, 62 parts of PhMI and 221 parts of acetonitrile were charged, and the mixture was thoroughly degassed by nitrogen bubbling, and polymerization was started in a thermostatic bath at 70 ° C. After 4 hours, the reaction was stopped by cooling to room temperature. The above polymerization solution was purified by reprecipitation from methanol / water = 90 / 10 (vol%) and vacuum dried to obtain polymer 4. As a result of analysis by gas chromatography, the reaction rate of polymer 4 was St 74% and PhMI 74%. The molecular weight of polymer 4 was Mn 13,100, Mw 31,100, and Mw / Mn was 2.37. St and PhMI correspond to the first monomer.

[0117] (Polymer 5:P(St / AN)-b-PAA) In a 1L flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 70 parts of polymer 2, 0.019 parts of ABN-E, 100 parts of acrylic acid (hereinafter also referred to as "AA") and 255 parts of acetonitrile were charged, thoroughly degassed by nitrogen bubbling, and polymerization was started in a thermostatic bath at 70 ° C. After 4 hours, the reaction was stopped by cooling to room temperature. The above polymerization solution was purified by reprecipitation from hexane and vacuum dried to obtain polymer 5. Analysis by gas chromatography showed that the reaction rate of AA was 74%. The molecular weight of polymer 5 after methyl esterification was Mn 24,800, Mw 35,500, and Mw / Mn 1.43. St and AN correspond to the first monomer.

[0118] [Table 1] St: styrene PhMI: N-phenylmaleimide AN: Acrylonitrile AA: Acrylic acid DBTTC: Dibenzyl trithiocarbonate 1-PEI: 1-phenylethyl iodide ABN-E: 2,2-azobis(2-methylbutyronitrile), manufactured by Nippon Finechem Co., Ltd., product name "ABN-E"

[0119] <Production Example of Polymer Microparticles> Example 1 Production Example 1 of Polymer Microparticles (Production of Polyacrylic Acid Microparticles Using Polymer 1) For the polymerization, a reactor equipped with a stirring blade, a thermometer, a reflux condenser, and a nitrogen inlet tube was used. 567 parts of acetonitrile, 2.20 parts of ion-exchanged water, 100.0 parts of AA, 0.90 parts of trimethylolpropane diallyl ether (manufactured by Daiso Co., Ltd., trade name "Neoallyl T-20"), 1 part of the above polymer (a1), and triethylamine equivalent to 1.0 mol% relative to the above AA were charged into the reactor. After the inside of the reactor was sufficiently replaced with nitrogen, the inside temperature was raised to 55°C by heating. After confirming that the inside temperature was stable at 55°C, 0.040 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., trade name "V-65") was added as a polymerization initiator, and the reaction liquid became cloudy, so this point was determined as the polymerization initiation point. The polymerization reaction was continued while maintaining the internal temperature at 55°C by adjusting the external temperature (water bath temperature), and the internal temperature was raised to 65°C when 6 hours had passed from the polymerization initiation point. The internal temperature was maintained at 65°C, and when 12 hours had passed from the reaction initiation point, the reaction rate of AA was 97%, and a reaction solution of a polymer in the form of a slurry in which particles were dispersed in the medium was obtained. After 12 hours, the reaction solution was cooled, and after the internal temperature had dropped to 25°C, 52.4 parts of lithium hydroxide monohydrate (hereinafter referred to as "LiOH·H2O") powder was added. After the addition, stirring was continued at room temperature for 12 hours, and a reaction solution of a block-type polyacrylic acid polymer in the form of a slurry in which particles of Li neutralized product (neutralization degree 90 mol%) of P(PhMI / St) were dispersed in the medium was obtained. The reaction solution obtained was centrifuged to settle the polymer fine particles, and the supernatant was removed. Thereafter, the precipitate was redispersed in acetonitrile of the same mass as the polymerization reaction solution, and the polymer fine particles were precipitated by centrifugation, and the washing operation of removing the supernatant was repeated twice. The precipitate was collected and dried at 80°C for 3 hours under reduced pressure conditions to remove the volatile matter, thereby obtaining block polymer R-1 (Li neutralization product of P(PhMI / St)-b-PAA-bP(PhMI / St)) as polyacrylic acid-based fine particles. Since the obtained polymer is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of the block polymer was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O of the carboxylic acid Li, which was 90 mol%, which was equal to the calculated value from the charge.

[0120] (Examples 2 to 19, Comparative Examples 1 to 2) The same procedure as in Example 1 was carried out except that the ingredients were changed as shown in Tables 2A and 2B, to obtain polyacrylic acid-based microparticles.

[0121] <Measurement of average particle size> For the polyacrylic acid-based microparticles obtained in each Example and Comparative Example, a field emission scanning electron microscope (FE-SEM, JSM-6330F manufactured by JEOL Ltd.) was used to obtain multiple images in which 50 to 100 particles could be observed per image. The images obtained were counted using image analysis software "WinROOF" manufactured by Mitani Shoji Co., Ltd. until the number of particles reached a total of 200, and the particle diameter (circle equivalent diameter) of the 200 particles was measured. This operation was also performed on another image, and the particle diameter of 200 particles was measured in the same manner. The average value of the particle diameters of these 400 particles in total was taken as the average particle diameter. The results are shown in Tables 2A and 2B.

[0122] <Viscosity measurement> The polyacrylic acid-based particles obtained in each Example and Comparative Example and ion-exchanged water were weighed into a 50cc container so that the concentration was 1.2wt% in terms of pure content, and set in a rotation / revolution type mixer (Thinky Corporation, Awatori Rentaro AR-250). Next, stirring (rotation speed 2000rpm / revolution speed 800rpm, 7 minutes) and degassing (rotation speed 2200rpm / revolution speed 60rpm, 1 minute) were performed to produce a hydrogel in which the polyacrylic acid-based particles were swollen in water. The temperature was controlled at 25°C for 30 minutes, and the viscosity after 90 seconds at 12 rpm using a B-type viscometer was taken as the aqueous solution viscosity.

[0123] <Haze measurement> The above 1.2 wt% hydrogel was used, and the solution was put into a cell and measured using a haze meter (instrument name NDH-2000, manufactured by Nippon Denshoku Co., Ltd.) to determine the haze. The total light transmittance of water was set to 100%. The results are shown in Tables 2A and 2B.

[0124] [Table 2A] [Table 2B] AA: Acrylic acid HEA: 2-hydroxyethyl acrylate T-20: Trimethylolpropane diallyl ether, manufactured by Daiso Co., Ltd., product name "Neoallyl T-20" TMPTMA: Trimethylolpropane trimethacrylate (Light Ester TMP, Kyoeisha Chemical) TEA: Triethylamine AcN: Acetonitrile V-65: 2,2'-azobis(2,4-dimethylvaleronitrile), manufactured by Wako Pure Chemical Industries, Ltd., trade name "V-65"

[0125] As shown in Tables 2A and 2B, the polyacrylic acid-based microparticles all had an average particle size of 0.20 μm or less, and as is clear from the results of Examples 1 to 19, they exhibited high thickening properties. Furthermore, their aqueous solutions exhibited high transparency. In contrast, Comparative Examples 1 and 2, which used polyacrylic acid-based microparticles with a particle size of more than 0.20 μm, were inferior in thickening properties and aqueous solution transparency.

[0126] Furthermore, from the results of Examples 1 to 19 and Comparative Examples 1 and 2, it was found that using 0.3 parts or more of the first polymer (polymer chain having living radical polymerization activity) based on the total mass of the second monomer is effective in suppressing the average particle size to 0.20 μm and the haze value, and that using the first polymer is effective in reducing the average particle size and the haze value.

[0127] It was also found that the first polymer had a good average particle size control effect whether it contained maleimide, acrylonitrile, maleic anhydride, or acrylic acid in addition to styrene. Furthermore, it was found that even if no crosslinkable monomer was used or only a small amount of the crosslinkable monomer was used, fine particles with a sufficiently small average particle size could be obtained, and in particular, when a small amount of the crosslinkable monomer was used, the transparency was excellent.

Claims

1. Polyacrylic acid microparticles, The polyacrylic acid-based microparticles contain a polyacrylic acid-based polymer that is derived from acrylic acid or a salt thereof and contains 10% by mass or more of a structural unit having a carboxy group or a salt of a carboxy group relative to the total mass of non-crosslinkable structural units, Polyacrylic acid-based microparticles having an average particle size of 0.01 μm or more and 0.20 μm or less, as determined by averaging the particle sizes of 400 particles in an image observed with a field emission scanning electron microscope.

2. 2. The polyacrylic acid-based microparticles according to claim 1, wherein the average particle size is from 0.01 μm to 0.15 μm.

3. 3. The polyacrylic acid-based microparticles according to claim 2, wherein the average particle size is from 0.01 μm to 0.10 μm.

4. 4. The polyacrylic acid-based microparticle according to claim 1, wherein the polymer contains 20% by mass or more of structural units derived from the acrylic acid.

5. 5. The polyacrylic acid-based microparticles according to claim 1, wherein the polymer is neutralized to a degree of neutralization of 50 mol % or more and 100 mol % or less.

6. The polyacrylic acid-based microparticles according to any one of claims 1 to 5, wherein the polymer is crosslinked by a crosslinkable monomer, and the amount of the crosslinkable monomer used is 0.03 mol % or more and 2 mol % or less based on the total amount of the non-crosslinkable monomer.

7. 7. The polyacrylic acid-based microparticle according to claim 1, wherein the polymer contains a polymer chain having living radical polymerization activity.

8. 8. The polyacrylic acid-based microparticle according to claim 7, wherein the molecular weight distribution of the polymer chains is 2.0 or less.

9. 9. The polyacrylic acid-based microparticle according to claim 7, wherein the content of the polymer chain in the polymer is 0.3% by mass or more and 30% by mass or less.

10. Polyacrylic acid microparticles, The polyacrylic acid-based microparticles contain a polyacrylic acid-based polymer that contains 20% by mass or more of structural units derived from acrylic acid or a salt thereof and having a carboxy group or a salt of a carboxy group relative to the non-crosslinkable structural units thereof, The polyacrylic acid-based fine particles, wherein a 1.2% by mass aqueous solution of the polyacrylic acid-based fine particles has a viscosity of 5,000 mPa·s or more and a haze value of 50% or less.

11. A thickener comprising the polyacrylic acid microparticles according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Production of hydrophilic polymer particle

    JP1992279604A

  • Aqueous coating composition and method for coating the same

    JP1994017000A

  • Method for producing spherical fine particles of crosslinked polymer

    JP2006282772A

  • Copolymer, charge controlling agent, toner, method for producing toner, toner feed cartridge, process cartridge, image forming apparatus and image forming method

    JP2008039941A

  • Method of producing toner, toner, developer and image forming method

    JP2010112983A